KUALITAS TUGAS AKHIR MAHASISWA - Busono, Mardiati (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2015)
The average length of srudy of he students of the Dept. of Special Education of the academic year 197/lW used to be 6.12 years and none of the students gradwted with a predicue cum laude. Research on study obstacles has not yet "Student been carried out. Research on Final Task Evalution of the Dept. Of Special Edtrcation of FIP IKIP in 1997’ las been geared ability of the sudentgs of tlat Dept. To do their toward idewifying obow the finnl ns.ra (thcsis or non-thesis). Based on he results of tlw above mentiorwd research the objective has been to accelerate and to amcliorate the sady, and to improve thc quality of thertnd task of the srudenu. Thc research appruch is contmt anatysis. Reseorch daa have been obnined the reports on the final task (thesis and non+hesis of thc academic year 195/j,9% and 195/199V. The dau vatidity of this research is the justification of the synchronization of the Ebel formuta. White the data anatysis is based on the urivariant anatysis. To descibe the ability and the inabiliry of the sndents in pursuing quatntive ond qmndntive their firnl apprrnch has beenused., The research indicued that 65% of the students had chnsen thesis as their tasks, and 35vo non-thesis as thcir firu| fiom tostcs a tastcs. Most of the proitems were concemed with psychological problcms, and research designs based on surveys elaborated into a.-postfacto antysis. Dau anatysis has been based on non-pramcaic stotistics. Textbool<s in the bolnsa Indonesia have been 1014 years old, and thc Engrish oncs lave been 20years oa., Thefinaltask of the sndeny courd be divided iwoTAS (thesis final tosks) and rABS (non thesis firwl tas/.s). For TAS there were 4l subjects and mostty on the btinds (12 subjects or 29,26%). while for TABS there are 23 subjea on menaily hondicapped(7 subjects or i0,43%). There v,as onty one subject on girted children or 4,34%. Ord il v.-s nat athesis, but afirai task (ion-thesis).TIis due to the gifted fact that there is rw Format Institute which hardle children.To obnin those subjects on gified children be tied at normal schoob and favoite schools.